Churning in thick labor markets. Evidence of heterogeneous responses along the skill and experience gradients - Stefan Leknes (Statistics Norway, Research Department, 2017)
Using a very large comprehensive matched employer-employee panel of the Norwegian workforce (19 million observations), I find a higher likelihood of job change across sectors and occupations, namely labor churning, in populous areas. Further investigation shows that this result is driven by high skilled groups, assumed to have more transferable skills. Moreover, educated urban workers are more likely to switch to sectors and occupations that they have prior experience with and that are similar in the use of human capital. Together, these novel results complement previous research by illuminating how the tradeoff between better labor matching and accumulating specific skills affect churning decisions for heterogeneous workers.
Keywords: J24; J63; R12; R23; 330; turnover; urban scale; human capital; sector; occupation